Optical quantum conformable recursional electroosmotic optimistic energy - Körpınar, Talat; Körpınar, Zeliha (Springer, 2024)
In this paper, we construct optical conformable normalization and conformable recursional of conformable magnetic field in spherical space. Thus, we obtain microfluidic optical conformable electroosmotic magnetical optimistic conformable energy. Finally, we design optical recursional conformable electroosmotic magnetical optimistic conformable energy.
Keywords: Optical recursion; Optical conformable normalization; Microfluidic microscale; Recursional optimistic density